Forage Plant Ecophysiology - Cory Matthew (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Forage plant ecophysiology has been described, perhaps mischievously, as the selective application of useful information from pure plant physiology research to provide human benefit through improved agricultural output. The intention of creating this Special Issue was to create a volume that future researchers will find user friendly and want to consult, while ensuring it is rich in scientific quality. Contributions were sought that provide a broad geographic representation and a snapshot of present knowledge and research on a range of forage species in use around the world.
English
Keywords: Alfalfa and salinity; Biomass partitioning and productivity; Alternative legumes; Tropical grasses; Sward dynamics and leaf plasticity